Anxiety and depression symptoms in recurrent painful renal lithiasis colic - Diniz,D.H.M.P. (2007)
Several studies have reported that symptoms of anxiety and depression are significantly associated with diseases characterized by painful crises. However, there is little information about the psychological aspects of recurrent painful episodes of renal stone disease. Our objective was to evaluate the association of symptoms of anxiety, depression and recurrent painful renal colic in a case-control study involving 64 subjects (32 cases/32 controls) matched for age and sex. Cases were outpatients with a confirmed diagnosis of nephrolithiasis as per their case history, physical examination, image examination and other laboratory exams. Patients had a history of at least two episodes within a 3-year period, and were currently in an intercrisis interval. The control group consisted of subjects seen at the Ophthalmology Outpatient Clinic of this University Hospital with only eye refraction symptoms, and no other associated disease. Symptoms of anxiety were evaluated by the State-Trait Anxiety Inventory and symptoms of depression by the Beck Depression Inventory. Statistically significant differences were observed between patients with nephrolithiasis and controls for anxiety state (P = 0.001), anxiety trait (P = 0.005) and symptoms of depression (odds ratio = 3.74; 95%CI = 1.31-10.62). The Beck Depression Inventory showed 34.5% of respondents with moderate and 6% with severe levels of depression. There was a significant linear correlation between symptoms of anxiety (P = 0.002) and depression (P < 0.001) and the number of recurrent colic episodes (anxiety-state: P = 0.016 and anxiety-trait: P < 0.001). These data suggest an association between recurrent renal colic and symptoms of both anxiety and depression.